早期评估NPM1突变阳性急性髓系白血病患者残留白血病水平的预后意义 (Zhonghua Xue Ye Xue Za Zhi, 2017)
OBJECTIVE: To explore prognostic significance of early assessment of minimal residual leukemia (MRD) in adult patients with de novo acute myeloid leukemia (AML) with mutated NPM1. METHODS: The response, NPM1 mutated transcript level after induction chemotherapy and the first 2 cycles of consolidation chemotherapy, disease-free survival (DFS) and overall survival (OS) in 137 patients with AML with NPM1 mutations of A, B and D were retrospectively analyzed. RESULTS: Data of 137 patients were collected, 67 were male, the median age was 49 years (16–67 years), 107 (78.1%) had normal karyotype, 57 (41.6%) had positive FLT3-ITD mutation, the median NPM1 mutated transcript level at diagnosis was 84.1%. Among the 134 evaluable patients, 115 (85.8%) achieved a complete remission (CR). Multivariate analyses revealed that WBC<100×10(9)/L (OR=0.3, 95% CI 0.1–0.9, P=0.027) and first induction therapy with “IA10” protocol (OR=0.3, 95% CI 0.1–0.8, P=0.015) were factors associated with achieving a CR. With a median follow-up period of 24 months (range, 2 to 91 months) in 77 survived CR patients, the probabilities of DFS and OS at 3 years were 48.0% and 63.9%, respectively. Multivariate analyses showed that positive FLT3-ITD (HR=3.2, 95% CI 1.6–6.7, P=0.002), high MRD level after 2 cycles of consolidation chemotherapy (NPM1 mutation transcript level <3-log reduction from the individual baseline, HR=23.2, 95% CI 7.0–76.6, P<0.001) and chemotherapy or autologous hematopoietic stem cell transplantation (auto-HSCT) rather than allogeneic HSCT (allo-HSCT) (HR=2.6, 95% CI 1.0–6.6, P=0.045) were the unfavorable factors affecting DFS, high MRD level at the time of achieving the first CR (NPM1 mutation transcript level <2-log reduction from the individual baseline, OR=2.5, 95% CI 1.0–6.1, P=0.040) and after 2 cycles of consolidation chemotherapy (HR=4.5, 95% CI 2.0–10.3, P<0.001) were the unfavorable factors affecting OS. Furthermore, DFS and OS rates at 3 years in those receiving chemotherapy or auto-HSCT were 39.7% and 59.1%, respectively; positive FLT3-ITD and high MRD level after 2 cycles of consolidation chemotherapy were independent factors associated with both shorter DFS (HR=3.5, 95% CI 1.6–7.6, P=0.002 and HR=8.9, 95% CI 3.8–20.7, P<0.001) and OS (HR=2.7, 95% CI 1.1–6.9, P=0.036 and HR=3.1, 95% CI 1.2–8.0, P=0.021); meanwhile, high MRD level at the time of achieving the first CR associated with shorter OS (HR=3.1, 95% CI 1.2–8.0, P=0.022). CONCLUSION: Positive FLT3-ITD mutation and high MRD level after induction or consolidation chemotherapy associated with poor outcomes in AML patients with mutated NPM1.